Violation of Human Right for Collateral Fraud in Sharia Financial Institution Based on Fiduciary Guaranty Law and Rahn Law - Endang Sriani; Farid Hasan; Sukron Ma'mun (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
Fiduciary law in Indonesia and the Islamic concept prohibit the use of collateral that is not one’s own and without the authorization of the owner, but the reality that occurs at BMT BM is not the case. This research aims to analyze the practice of using objects on behalf of others as collateral for ijarah multijasa financing in sharia financial institutions from the perspective of Fiduciary Guarantee Law and Rahn Law. This research is a field study with a legal approach. The empirical results show that although it has been regulated in the law, the use of objects that are not owned and without the permission of the owner as collateral still occurs. There is a way to circumvent the rules, particularly when it comes to the creditor’s obligation to register fiduciary objects but reluctance to do so. As a result, protecting third parties is not achieved. The findings indicate that, to ensure that the parties’ rights are still protected, the government must create a legislation on fiduciary that will take into account debtors with tiny nominal debts who feel burdened by the costs of registering fiduciary objects, as was the case in BMT BM.